Pengaruh Financial Technology (FinTech) Lending dan Literasi Keuangan terhadap Kinerja Keuangan UMKM di Kota Majelengka Pasca Pandemi - Saebah, Nur (GEMA EKONOMI, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Majelengka City face challenges in post-pandemic financial recovery, with access to capital and financial literacy being critical factors. The development of Financial Technology (FinTech) Lending offers alternative financing solutions, but its effectiveness is strongly suspected to be influenced by the level of financial literacy of MSMEs. This study aims to analyze the direct influence of FinTech Lending and financial literacy on MSME financial performance and examine the role of financial literacy as a moderator of the relationship between FinTech Lending and financial performance. This quantitative study used a cross-sectional study design. Data were collected through questionnaires from 400 MSMEs in Majelengka City selected using stratified random sampling. Data were analyzed using Moderated Regression Analysis (MRA) with the help of SPSS. The results demonstrate that FinTech Lending and financial literacy positively and significantly influence MSME financial performance. The main findings reveal that financial literacy acts as a significant moderator and strengthens the positive influence of FinTech Lending on financial performance. It is concluded that financial literacy is a determining factor that strengthens the benefits of FinTech Lending for MSME performance. These findings emphasize the importance of integrated policies and programs, namely not only encouraging digital financial inclusion but also simultaneously increasing the financial literacy capacity of MSMEs.